Dynamics of Work-Limitation and Work in Australia - Oguzoglu, U (My University, 2007)
This paper examines the impact of self-reported work-limitation on the employment of the Australian working age population. Five consecutive waves of the Household, Income and Labour Dynamics in Australia (HILDA) Survey are used to investigate this relationship. A two-equation dynamic panel data model demonstrates that persistence and unobserved heterogeneity play an important role in the work-limitation reporting and its effect on work. Unobserved factors that jointly drive work-limitation and work are also shown to be crucial, especially for women.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Labour market; Employment and unemployment